The Effect of Various Tillage Systems on Productivity of Narrow-Leaved Lupin-Winter Wheat-Winter Triticale-Winter Barley Rotation - Katarzyna Panasiewicz; Agnieszka Faligowska; Grażyna Szymańska; Jerzy Szukała; Karolina Ratajczak; Hanna Sulewska (Agronomy, 2020)
Legumes are increasingly important crops in most European Union (EU) countries because of the growing demand for feed protein, and also because they have been shown to improve the characteristics of soil. The main part of the crop rotation is taken up by cereals, but they are connected with undesirable side effects, such as the unilateral utilization of ingredients and the heightened risk of plant diseases, e.g., Fusarium. Simplification of farming methods has become increasingly popular as growers search for cheaper production technologies. However, the effects of long-term simplification in tillage practices on the production and economics of narrow-leafed lupine (NL) cultivation have not been studied. In 2012−2016, we carried out a field experiment in Poland with a one-factorial design with four replications. The aim of the experiment was to evaluate the productivity effect of conventional tillage (CT), reduced tillage (RT) and no-tillage (NT) on NL-winter wheat (WW)-winter triticale (WT)-winter barley (WB), rotation. Our results show that the productivity of this crop rotation was lower under RT and NT systems than under CT. From a practical point of view, the reduction of cultivation in rotation with 75% of cereals caused a decrease in yield in all species, which can result in resign of using the RT and NT in conditions of Albic Luvisols soil, as classified according to the World Reference Base (WRB). The highest incomes were found when the CT system was used with NL. Although income losses exceeded the value of savings in both minimalized soil tillage systems (RT and NT), all tillage systems of NL were profitable.